Nutrition security and homestead gardeners: Evidence from the Himalayan mountain region - Patra, Nirmal Kumar; Nina, Nich; Pathak, Tapan B.; Karak, Tanmoy; Babu, Suresh Chandra (MDPI, 2025)
Background: Addressing undernutrition and malnutrition requires a multi-pronged approach targeting different populations with appropriate interventions. Knowledge and perception (K&P) of Individuals and communities about nutrition to human health relationship/continuum is a prerequisite for addressing malnutrition in rural and mountain communities. Assessing K&P is essential for developing strategic interventions to up-scaling K&P of communities and achieving nutrition security. Homestead gardens are a proven intervention for achieving nutrition security for all family members of gardeners. Methods: This paper includes homestead gardeners from the Himalayan Mountain Region (HMR) as respondents. We developed a scale to assess the K&P of respondents, based on ratings from 20 judges. A total of 134 issues/items have been retained in the scale from macronutrients, micronutrients, minerals, and vitamins. A framework has also been developed and adopted for the study. A knowledge and perception index (KPI) has been developed based on the respondents’ responses. We have reviewed and analysed the national policy interventions for augmenting the K&P of the study community to achieve nutrition security. Results: The nutrition K&P of respondents are inadequate and far from the desirable level. Policy review and analysis indicate that the creation of K&P in the community to contribute to self and family nutrition security was previously highly neglected. Conclusions: The policy process of national, state, and county/district-level development sectors in developing countries under the HMR may take the initiative to ensure self-nutrition security by creating K&P of the community on nutrition issues. The designed scale is prudent requires testing and validation for measuring farmers’ K&P on nutrition, which may be adopted in future studies and policymaking not only nationally but also from an international perspective.